Letters as Loot. A sociolinguistic approach to seventeenth- and eighteenth-century Dutch - Marijke J. van der Wal (Advances in Historical Sociolinguistics, 2014)
The study of letter writing is at the heart of the historical-sociolinguistic enterprise. Private letters, in particular, offer an unprecedented view on language history. This book presents an in-depth study of the language of letters focussing on a unique collection of Dutch private letters from the seventeenth and eighteenth centuries, which comprises letters from the lower, middle and upper ranks, written by men as well as women. The book discusses the key issues of formulaic language and the degree of orality of private letters, it questions the importance of letter-writing manuals, and reveals remarkable patterns of social, regional and gender variation in a wide range of linguistic features. Arguing for writing experience as an important factor in historical linguistics generally, the book offers numerous new perspectives on the history of Dutch. The monograph is of interest to a wide readership, ranging from scholars of historical linguistics, sociolinguistics, Germanic linguistics, sociology and social history to (advanced) graduate and postgraduate students in courses on language variation and change.